Method development for mono‐ and disaccharides monitoring in cell culture medium by capillary and microchip electrophoresis. Issue 9 (12th October 2021) - van der Burg, Debbie; Josefsson, Leila; Mikkonen, Saara; Chotteau, Véronique; Emmer, Åsa; Wätzig, Hermann; Sänger‐van de Griend, Cari E.
Abstract: The rapidly growing, competitive biopharmaceutical market requires tight bioprocess monitoring. An integrated, automated platform for the routine online/at‐line monitoring of key factors in the cell culture medium could greatly improve process monitoring. Mono‐ and disaccharides, as the main energy and carbon source, are one of these key factors. A CE‐LIF method was developed for the analysis of several mono‐ and disaccharides, considering requirements and restrictions for analysis in an integrated, automated monitoring platform, such as the possibility for miniaturization to microchip electrophoresis. Analysis was performed after fluorescent derivatization with 8‐aminopyrene‐1, 3, 6‐trisulfonic acid. The derivatisation reaction and the separation BGE were optimized using design of experiments. The developed method is applicable to the complex matrix of cell culture medium and proved transferable to microchip electrophoresis.